Presence of Candida spp. in the oral cavity of heart transplantation patients - Ribeiro, Patricia Monteiro [UNESP]; Bacal, Fernando; Koga-Ito, Cristiane Yumi [UNESP]; Junqueira, Juliana Campos [UNESP]; Cardoso Jorge, Antonio Olavo [UNESP] (Universidade de São Paulo (USP), Faculdade de Odontologia de Bauru, 2011)
Candida spp. can lead to infections or even fungal sepsis particularly among immunocompromized individuals. Objective: The aim of the present study was to analyze the presence of Candida spp. among patients subjected to orthotopic heart transplantation. Material and Methods: Oral rinses from 50 patients subjected to orthotopic heart transplantation, aged 13 to 70 years, 40 males and 10 females, were examined. Sex-age-oral conditions matched-control included 50 individuals who were not subjected to any kind of transplantation and were not immunocompromized for any other reason. Counts of yeasts were expressed as median values of logarithm of cfu/mL and were statistically compared by Mann-Whitney's test. The heart transplant and control groups were compared for the presence of Candida spp. by chi-square test (p < 0.05). Results: The results showed statistically significant difference (p = 0.001) in the prevalence of Candida spp. between the transplantation and control groups. Counts of yeasts (cfu/mL) in the transplanted group were significantly higher than in the control group (p = 0.005). Candida albicans was the most prevalent species isolated from both groups. Conclusions: It was concluded that Candida yeast counts were higher in the heart transplant recipients than in the controls. There was higher variation of Candida species among the heart transplant patients and the most frequently isolated samples were: Candida albicans, Candida glabrata and Candida tropicalis. Isolates of Candida dubliniensis was not found in either of the groups.
Keywords: Candida; Heart transplantation; Oral; Fungal infections